Administration of eicosapentaenoic acid may alter lipoprotein particle heterogeneity in statin-treated patients with stable coronary artery disease: A pilot 6-month randomized study. Issue 5 (November 2020) - Tani, Shigemasa; Yagi, Tsukasa; Matsuo, Rei; Kawauchi, Kenji; Atsumi, Wataru; Matsumoto, Naoya; Okumura, Yasuo
Highlights: Additional eicosapentaenoic acid (EPA) therapy altered lipoprotein heterogeneity. EPA seems to favorably alter lipoprotein heterogeneity in statin-treated patients. EPA/arachidonic acid ratio may indicate the changes in lipoprotein heterogeneity. EPA added to statin therapy is effective for the prevention of coronary artery disease. Abstract: Background: We hypothesized that the addition of eicosapentaenoic acid (EPA) to ongoing statin therapy could change the particle heterogeneity of low-density lipoprotein (LDL) and high-density lipoprotein (HDL) particles, even in stable coronary artery disease (CAD) patients. Methods: We assigned CAD patients already receiving statin therapy to one of two groups: an EPA group (1800 mg/day; n = 30) and a control group (n = 30). A gel permeation high-performance liquid chromatography method was used to measure the particle concentration and number of lipoprotein subclasses. Results: In the EPA group, significant decreases of both the concentration and number of medium LDL ( p = 0.0002 and 0.0001), small LDL ( p = 0.0004 and 0.0005) and very small LDL ( p = 0.0005 and 0.002) particles were observed. Conversely, the concentration and number of large HDL particles increased significantly ( p = 0.024 and 0.048). The concentration of very large HDL particles also increased significantly ( p = 0.028). Furthermore, significant correlations between the variables that showed significant changes in the LDL and HDL particle subclasses, and the EPA/arachidonic acid (AA) ratio were found. No other significant associations of lipoprotein particle heterogeneity with the serum EPA/AA ratio were noted in either the control group or the EPA group. Interestingly, univariate and multivariate regression analyses revealed that increased serum lecithin–cholesterol acyltransferase activity, a key enzyme of HDL cholesterol efflux, was a predictor for increased above-mentioned HDL particles subclasses. Conclusions: Administration of EPA might alter both LDL and HDL particle heterogeneity, causing decreased concentration and number of smaller LDL particles and increased concentration and number of larger HDL particles. Furthermore, addition of EPA to ongoing statin therapy appears to be capable of increasing the EPA/AA ratio, which might have an anti-atherosclerotic effect on lipoprotein particle heterogeneity, even in stable CAD patients with well-controlled serum lipid levels. Clinical Trial Registration: UMIN (http://www.umin.ac.jp/ ) Study ID: UMIN000010452.